Social crises: A network model approach - Cárdenas, Juan Pablo (2018)
Crisis, conflict and complexity are concepts that are deeply related in the evolutionary history of social dynamical systems. The spontaneous increase of complexity of adaptive systems, including social systems, entails critical processes where the organization of the system, or part of it, is questioned. In this study we address the phenomenon of social crises through models of society based in networks that combine the increase in complexity with the clash of forces in conflict which could lead to a crisis for the system. The simulations suggest that there is a positive correlation between the increase in the complexity of the system and the emergence of crises as a complex phenomenon itself where its mitigation can have unexpected results.